Workshop Pembuatan Modul Ajar Pembelajaran Mendalam Menggunakan AI - Mas’ud B; Malik, Marwati Abd.; Agustini; Asrida; Dewi, Fitriani; Ramadhan, Fitriadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This workshop aims to provide a platform for Mathematics teachers in Parepare City to develop their skills in designing teaching modules integrated with deep learning approaches using AI technology. The activity is organized by Pre-service Teacher Professional Education (PPG) students from Cohort 2 of 2024 at the Faculty of Teacher Training and Education, Muhammadiyah University of Parepare, in collaboration with the Department of Education and Culture of Parepare City and the Mathematics MGMP (Subject Teacher Forum) for junior high schools across the city. The method used in this workshop includes hands-on sessions, discussions, and Q&A with expert speakers. The workshop was attended by 37 teachers, reflecting active participation and enthusiasm, indicating a strong motivation among the teachers to enhance their skills. The materials presented included direct application demonstrations on how to create teaching modules using AI technology, allowing the teachers to apply the knowledge directly on their own laptops.